The expressive forms of Xu Bing’s Neo English calligraphy / Xie Jinfu - Xie , Jinfu (2020)
Xu Bing is active in the contemporary art world and a famous calligraphy artist and painter who held many individual art exhibitions in New York New Art Museum, Czech National Museum and other famous international art institutions. In 1999, he was the recipient of a MacArthur Fellowship in recognition of his "significant contribution to society, particularly in printmaking and calligraphy". Xu Bing created a kind of new square character which combined English alphabets with Chinese calligraphy strokes and named it Neo English calligraphy. A series of Neo English calligraphy artwork was produced which theoretically influenced by the Chinese traditional philosophy and transformed into Chinese calligraphy which makes many experts, scholars and even the general public interested in its "value" and "innovation". This paper focuses on the expressive form of Neo English calligraphy and analyses its social impact.